Neurorights and constitutional dogmatics: critical approach from article 19 n°1, paragraph 5° (Justicia &Derecho, 2024)
This article analyses the notion of “neuro-rights” in the following way: first, by interpreting the new final paragraph of article 19 N°1 of the Chilean constitutional text reformed by Law 21.383 that modifies the Fundamental Charter, in order to establish scientific and technological development at the service of people; secondly, by explaining the concerns that constitutional dogmatics has highlighted regarding the regulation and protection of the so-called “neuro-rights”; thirdly, I will make some critical comments on the understanding of the constitutional reform referred to and the articulation of the incipient dogmatic concern for the intersection between technological and legal development.
Keywords: neurorights; legal interpretation; constitutional dogmatics; Constitutional amendment; Constitution